Investment Decision Based on Financial Performance Analysis and Market Approach Valuation of Indonesian Construction Sector - Makarim, Rahmat Faikar; Noveria, Ana (Journal of Business and Management, 2014)
Investment is one of the tools for a company in gaining additional capital. This research will seeks the analysis of company financial performance and valuation as the fundamental tools in making investment decision on Indonesia construction sector, represented by 5 listed construction sector companies, which are PT Adhi Karya (ADHI), PT Wijaya Karya (WIKA), PT Nusa Konstruksi Enjiniring (DGIK), PT Total Bangun Persada (TOTL), and PT Surya Semesta Internusa (SSIA). By analyzing the financial performance, could be obtained the financial health condition of the company that will represent the company future to attract the investors. While the market approach valuation is used to see whether the company is undervalued or overvalued. Due to the development of Indonesia into a developed country, this sector has a high demand of work that make it always able to generate high net sales and profit for the past few years. This makes this sector one of the most secure stock to investing in. Moreover, the under value of their share price will give the investors possibilities of high return and probable increase of stock price on the future.Keywords: Construction sector, financial ratios, valuation, market approach, financial performance.